2010
DOI: 10.1182/blood-2009-10-250209
|View full text |Cite
|
Sign up to set email alerts
|

A self-inactivating lentiviral vector for SCID-X1 gene therapy that does not activate LMO2 expression in human T cells

Abstract: IntroductionX-linked severe combined immunodeficiency (SCID-X1) is caused by loss-of-function mutations in the ␥ c gene (also known as IL2RG), 1,2 which encodes the common ␥-chain (␥ c ) subunit for the IL2, IL4, IL7, IL9, IL15, and IL21 receptors and is required for signal transduction with these cytokines. 3 Human SCID-X1 is characterized by lack of T, natural killer (NK) cells, and nonfunctional B cells and is fatal early in life from progressive infections if left untreated. Allogeneic stem cell transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 50 publications
2
104
0
Order By: Relevance
“…Although SIN vectors were developed from earlier retroviral [62] or lentiviral vectors [63] to reduce the risk of oncogenicity in SCID-X1 gene therapy, genotoxicity unrelated to mutations in gene insertion regions or γc chain gene overexpression have been reported with lentiviral vectors in recent years, and it seems that more sophisticated vector development is required [64].…”
Section: Scid-x1mentioning
confidence: 99%
“…Although SIN vectors were developed from earlier retroviral [62] or lentiviral vectors [63] to reduce the risk of oncogenicity in SCID-X1 gene therapy, genotoxicity unrelated to mutations in gene insertion regions or γc chain gene overexpression have been reported with lentiviral vectors in recent years, and it seems that more sophisticated vector development is required [64].…”
Section: Scid-x1mentioning
confidence: 99%
“…Vector copy number (VCN) was measured using quantitative PCR method. 26 One clone with an estimated VCN of 19 was chosen for further experiments. VCN was verified by Southern blot analysis and fluorescence in situ hybridization using a vector-specific probe.…”
Section: Generation Of Jurkat Clone With Defined Vismentioning
confidence: 99%
“…We transduced Jurkat cells, a widely available human T cell line, with our CL20-4i-EF1a-hccOPT lentiviral vector 26,30 at high multiplicity of 100 and isolated single cell clones with defined copy numbers. As a standard, we chose one clone containing 19 copies of the vector genome per cell when measured by qPCR and Southern blot analysis for proviral DNA genome copies.…”
Section: Generation Of a Standard Human Clonal Cell Line With Multiplmentioning
confidence: 99%
See 1 more Smart Citation
“…38 A novel stable packaging cell line was derived at SJCRH and used to produce the clinical-grade vector. 39 Extensive preclinical safety studies were done that demonstrated undetectable genotoxocity from the vector, in contrast to the ␥-RVs with intact LTR used as a positive control.…”
Section: Xscidmentioning
confidence: 99%